TWIST1 유전자의 돌연변이가 확인된 Saethre-Chotzen 증후군 2례 - 고정민(Jung Min Ko); 양정아(Jung-Ah Yang); 정선용(Seon-Yong Jeong); 윤수한(Soo Han Yoon) (Journal of genetic medicine, 2011)
Saethre-Chotzen syndrome is an autosomal dominant craniosynostosis syndrome, usually involving unior bilateral coronal synostosis and mild limb deformities, and is induced by loss-of-function mutations of the TWIST1 gene. Other clinical features of this syndrome include ptosis, low-set ears, hearing loss, hypertelorism, broad great toes, clinodactyly, and syndactyly. The authors of the present study report 2 children with clinical features of Saethre-Chotzen syndrome who showed mutations in the TWIST1 gene, and is the first molecular genetic confirmation of Saethre-Chotzen syndrome in Korea. The molecular genetic testing of the TWIST1 gene for patients with coronal synostoses is important to confirm the diagnosis and to provide adequate genetic counseling. Saethre-Chotzen 증후군은 상염색체 우성의 유전 방식을 보이는 두개골유합증후군(craniosynostosis)의 하나로, 원인 유전자는 TWIST1로 알려져 있다. Saethre-Chotzen 증후군의 임상 증상은 두개골유합증 중에서도 특히 관상봉합(coronal suture)이 편측 혹은 양측으로 조기에 폐쇄되는 것이 특징적이며, 이외에도 안검하수, 낮게 위치한 귀, 청력 소실, 손발가락의 기형 등 다양한 이상이 동반될 수 있다. 저자들은 양측성 관상봉합 두개골유합증과 특징적인 얼굴 모습, 다양한 동반 기형을 보인 두 명의 환자에서 TWIST1 유전자의 원인 돌연변이를 각각 확인하고 Saethre-Chotzen 증후군을 확진하였기에, 국내에서 처음으로 보고하는 바이다. 특히, TWIST1 유전자 분석은 관상봉합 유합증을 보이는 환자에서 질환을 확진하고, 및 환자와 가족에 대한 적절한 유전 상담을 제공하는데 유용한 검사로 생각된다.